Illicium verum Extract and Trans-Anethole Attenuate Ovalbumin-Induced Airway Inflammation via Enhancement of Foxp3+ Regulatory T Cells and Inhibition of Th2 Cytokines in Mice - Sung, Yoon-Young; Kim, Seung-Hyung; Kim, Dong-Seon; Lee, Ji-eun; Kim, Ho Kyoung (Mediators of Inflammation, 2017)
Illicium verum is used in traditional medicine to treat inflammation. The study investigates the effects of IVE and its component, trans-anethole (AET), on airway inflammation in ovalbumin- (OVA-) induced asthmatic mice. Asthma was induced in BALB/c mice by systemic sensitization to OVA, followed by intratracheal, intraperitoneal, and aerosol allergen challenges. IVE and AET were orally administered for four weeks. We investigated the effects of treatment on airway hyperresponsiveness, IgE production, pulmonary eosinophilic infiltration, immune cell phenotypes, Th2 cytokine production in bronchoalveolar lavage, Th1/Th2 cytokine production in splenocytes, forkhead box protein 3 (Foxp3) expression, and lung histology. IVE and AET ameliorated OVA-driven airway hyperresponsiveness (p<0.01), pulmonary eosinophilic infiltration (p<0.05), mucus hypersecretion (p<0.01), and IL-4, IL-5, IL-13, and CCR3 production (p<0.05), as well as IgE levels (p<0.01). IVE and AET increased Foxp3 expression in lungs (p<0.05). IVE and AET reduced IL-4 and increased IFN-γ production in the supernatant of splenocyte cultures (p<0.05). Histological studies showed that IVE and AET inhibited eosinophilia and lymphocyte infiltration in lungs (p<0.01). These results indicate that IVE and AET exert antiasthmatic effects through upregulation of Foxp3+ regulatory T cells and inhibition of Th2 cytokines, suggesting that IVE may be a potential therapeutic agent for allergic lung inflammation.